Frequency of Different Neuropsychiatric Manifestations of Systemic Lupus Erythematosus at a Tertiary Care Hospital in Pakistan - Ullah, Naeem; Adnan, Saqib; Mustafa, Syed Hassan; Khan, Suleman; Hussain, Ibrar; Ullah, Saleem (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of different neuropsychiatric manifestations of systemic lupus erythematosusStudy Design: Cross-sectional study.Place and Duration of Study: Division of Rheumatology Lady Reading Hospital, Peshawar Pakistan, from Sep 2020 to Feb 2021.Methodology: 31 patients who fulfilled the 2019 ACR/EULAR criteria for SLE diagnosis were included in the study. Different features of neuropsychiatric manifestations of systemic lupus erythematosus were recorded on a proforma.Results: Our study sample included 27 females and four males. Most of the patients were young, with a mean age of 23.12 ± 10.74 years. All patients had positive Anti-nuclear antibodies (100%), while anti-double standard DNA antibody was found in 21 patients (67. 74%). Seizures were the most common neuropsychiatric feature, i.e., found in 18 patients (58%), followed by headache (25.8%), acute confusional state (25.8%) and CNS demyelinating disease (19.3%).Conclusion: We found that seizures, headache and acute confusional state were the most common neuropsychiatric manifestations of systemic lupus erythematosus.